2018
DOI: 10.1021/jacs.8b05366
|View full text |Cite
|
Sign up to set email alerts
|

Differential Conformational Dynamics Encoded by the Linker between Quasi RNA Recognition Motifs of Heterogeneous Nuclear Ribonucleoprotein H

Abstract: Members of the heterogeneous nuclear ribonucleoprotein (hnRNP) F/H family are multipurpose RNA binding proteins that participate in most stages of RNA metabolism. Despite having similar RNA sequence preferences, hnRNP F/H proteins function in overlapping and, in some cases, distinct cellular processes. The domain organization of hnRNP F/H proteins is modular, consisting of N-terminal tandem quasi-RNA recognition motifs (F/HqRRM1,2) and a third C-terminal qRRM3 embedded between glycine-rich repeats. The tandem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
(146 reference statements)
1
15
0
Order By: Relevance
“…Heteronuclear single quantum coherence (HSQC) titrations, wherein uniformly 15 N-labled HqRRM1,2 was titrated with unlabeled 5=-AGGGC-3=, revealed broadening of the NMR signals for HqRRM1,2 and indicated that binding specificity is governed by both the qRRM1 and qRRM2 domains ( Fig. 9B and C), similar to our previous observations with 5=-AGGGU-3= (54).…”
Section: Clip-seq Experimentssupporting
confidence: 87%
See 1 more Smart Citation
“…Heteronuclear single quantum coherence (HSQC) titrations, wherein uniformly 15 N-labled HqRRM1,2 was titrated with unlabeled 5=-AGGGC-3=, revealed broadening of the NMR signals for HqRRM1,2 and indicated that binding specificity is governed by both the qRRM1 and qRRM2 domains ( Fig. 9B and C), similar to our previous observations with 5=-AGGGU-3= (54).…”
Section: Clip-seq Experimentssupporting
confidence: 87%
“…This notion is consistent with the model that hnRNPs can loop out entire exons (60), which would require a minimum of two binding sites surrounding the exon. Previously, we showed that the N-terminal HqRRM1,2 didomain of hnRNP H1 exists in a conformational equilibrium between compact and extended structures (54). The compact structure has both qRRMs juxtaposed, generating a continuous RNAbinding surface that would accommodate only a single isolated G-tract element.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins do not contain the typical RNP-1 and RNP-2 consensus sequences but are capable of binding some nucleotide sequences [88,89]. Nevertheless, qRRM domains bind to G-tract RNA and participate in the regulation of the alternative splicing of pre-mRNAs [90,91].…”
Section: General Properties Of Several Main Human Hnrnps Involved mentioning
confidence: 99%
“…X-ray-crystallography and NMR studies show that the qRRM1-qRRM2 domains of HNRNPH1/H2 switch between a compact state, resulting in RNA recognition by both qRRMs of a single G-rich sequence and an extended state where it can bind to two different G-tracts. HNRNPH1/H2 primarily form compact states, and the linker between the two qRRMs remains rigid, differing from HNRNPF, which exhibits a flexible and extended state (44).…”
Section: Introductionmentioning
confidence: 99%
“…X-ray-crystallography and NMR studies show that the qRRM1-qRRM2 domains of HNRNPH1/H2 switch between a compact state, resulting in RNA recognition by both qRRMs of a single G-rich sequence and an extended state where it can bind to two different G-tracts. HNRNPH1/H2 primarily form compact states, and the linker between the two qRRMs remains rigid, differing from HNRNPF, which exhibits a flexible and extended state (44). Consistent with the assertion that the binding of HNRNPH/F proteins inhibits rG4 formation (16), Dominguez and co-workers showed that a single qRRM domain of HNRNPF could alter the splicing of the BCL-X pre-RNA by inhibiting the formation of the intramolecular bonds required for the formation of a secondary structure (43).…”
Section: Introductionmentioning
confidence: 99%